Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan Media Video Pembelajaran terhadap Kemampuan Penalaran Matematis Siswa - Amri, Khoirul; Andhany, Ella (Jurnal Pendidikan Matematika : Judika Education, 2024)
This study aims to determine the effect of implementing a problem-based learning model assisted by video learning media on the mathematical reasoning abilities of class VIII students of MTS PP Tarbiyah Islamiyah Hajoran. The method used in this study is a quasi-experimental with a pretest-posttest control group design. The subjects of the study involved 64 students, with class VIII A as the experimental class using a problem-based learning model, and class VIII B as the control class. Data were collected through a mathematical reasoning ability test and analyzed using statistical tests. The results showed a significance value (Sig.) of 0.000, which is smaller than the significance level of α = 0.05. This shows that there is a significant difference in students' mathematical reasoning abilities between the experimental class and the control class, so that the problem-based learning model assisted by video media has proven effective in improving students' mathematical reasoning abilities. Keywords: Problem-Based Learning Model, Learning Video Media, Reasoning Ability.